2003
DOI: 10.1111/j.1467-8268.2003.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Currency Devaluation Improve the Trade Balance in the Long Run? Evidence from Malawi

Abstract: This paper explores the impact of nominal exchange rate devaluation on the trade balance for Malawi. A small-open economy IS-LM aggregate supply model of Malawi estimated using time series data covering the period 1967-96 is used in the simulation analysis. The results of the simulation experiment show that devaluation helps to improve export performance and to curtail the growth of imports in the long run, which lead to improvement in the trade balance position. The results provide evidence supporting the vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…These studies (refer Appendix 9.1) have largely adopted either panel data models (Berman & Berthou, 2009;Santos-Paulino, 2002); or undertaken time series analysis (Owen, 2005). Musila and Newark (2003) examine four empirical approaches to such research. Such approaches include a 'before-and-after' approach, which examines changes in the trade balance at the time of devaluation; a control group approach, where a sample of devaluing countries are compared to a control group of non-devaluing countries; a time series approach; and a macro-simulation model (Musila & Newark, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies (refer Appendix 9.1) have largely adopted either panel data models (Berman & Berthou, 2009;Santos-Paulino, 2002); or undertaken time series analysis (Owen, 2005). Musila and Newark (2003) examine four empirical approaches to such research. Such approaches include a 'before-and-after' approach, which examines changes in the trade balance at the time of devaluation; a control group approach, where a sample of devaluing countries are compared to a control group of non-devaluing countries; a time series approach; and a macro-simulation model (Musila & Newark, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Research done by Bautista (1982), Abeysinghe and Yeok (1998), Musila and Newark (2003) and Auer and Chaney (2009) found that currency weakness improves export performance. However, contrary findings were presented in studies done by Lizondo and Montiel (1989), Calvo and Reinhart (2000), Musila (2002), Frankel (2005 and Berman and Berthou (2009), where currency weakness was found to have either a negative effect on export performance, or little effect.…”
Section: The Scope Of the Researchmentioning
confidence: 99%
See 3 more Smart Citations